Landslide Hazard Mapping in Panchase Mountain of Central Nepal: DOI: 10.32526/ennrj.18.4.2020.37 - Budha, Padam Bahadur; Rai, Pawan; Katel, Prem; Khadka, Anu (Environment and Natural Resources Journal, 2020)
Numerous slope failures have been noticed in the Panchase region of central Nepal posing threats to people and biodiversity. Considering the need to reduce landslide risks, this research determined the spatial extent of landslide hazard degrees in the Panchase area. The research site, with an area of 278.324 km2, consists of parts of the Kaski, Parbat, and Syangja Districts. A Statistical Index Method was used for hazard analysis that produced weights. Positive weight values for each factor class represented a higher hazard and vice versa. An inventory of the study area identified 556 landslides measuring 1.511 km2 indicating a landslide density of 2 per km2 area. Thirteen percent (36.18 km2) of the total experimental area was rated as a very high hazard zone. Similarly, the area occupied by high hazard and moderate hazard zones were 77.66 km2 (28%), and 81.83 km2 (29%) respectively. The validation showed that the method can produce results with of accuracy of 82.8%. This indicated the hazard assessment process is acceptable and replicable. The factor classes having greater influence for higher landslide hazard are: near the streams, near the roads, barren or grassland, land with phyllite bedrocks, land receiving rainfalls greater than 4,000 mm, lands with an elevation range from 1,000 m to 1,500 m, slopes steeper than 30°, and south-facing slope. During risk management work by local authorities, considerations should be given to these factors and areas with higher hazards.